TANTANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM PERLINDUNGAN KONSUMEN - Edwin Yuliska (Ensiklopedia of Journal, 2025)
The Consumer Dispute Resolution Agency (BPSK) has a strategic role in resolving disputes between consumers and business actors outside the court. However, in practice, BPSK faces various challenges that hinder its effectiveness in providing consumer protection. This study aims to analyze the challenges faced by BPSK, including limited regulations, low public awareness, minimal resources, slow dispute resolution processes, and low compliance of business actors with BPSK decisions. The research method used is a normative legal approach with an analysis of applicable laws and regulations and case studies related to consumer dispute resolution in Indonesia. The results of the study indicate that although BPSK has a strong legal basis through Law Number 8 of 1999 concerning Consumer Protection, its implementation still experiences various obstacles. Keywords: Challenges, Consumer Dispute Resolution Agency (BPSK), Consumer Protection